Oxyhemoglobin Saturation Overshoot Following Obstructive Breathing Events Mitigates Sleep Apnea-Induced Glucose Elevations - Pham, Luu V.; Schwartz, Alan R.; Jun, Jonathan C. (Frontiers in Endocrinology, 2018)
Background: Obstructive sleep apnea (OSA) and nocturnal hypoxia are associated with disturbances in glucose regulation and diabetes. Temporal associations between OSA, oxygenation profiles and glucose have not been well-described. We hypothesized that oxyhemoglobin desaturation during apneic events and subsequent post-apnea saturation overshoot predict nocturnal glucose. Methods: In 30 OSA patients who underwent polysomnography while subjected to CPAP withdrawal, we characterized SPO2 swings by frequency, desaturation depth, and overshoot height relative to baseline. We examined the associations between frequently sampled glucose and SPO2 swings during the preceding 10 min. We developed multi-variable mixed effects linear regression to examine the independent associations between glucose and each level of these SPO2 swings, while controlling for OSA severity. Results: Desaturation depth was not associated with glucose (p > 0.05). In contrast, overshoot was associated with glucose in a dose-dependent manner. Each SPO2 peak that did not rise to within 1% of baseline was associated with incremental glucose elevations of 0.49 mg/dL (p = 0.01), whereas peaks that exceeded baseline by >1% were associated with glucose reductions of 0.46 mg/dL. Overshoot remained an independent predictor of glucose after adjustment for mean SPO2 and OSA severity (p > 0.05). Conclusions: Vigorous SPO2 improvements after apneic events may protect patients against OSA-related glucose elevations.